2018
DOI: 10.1183/23120541.00042-2018
|View full text |Cite
|
Sign up to set email alerts
|

Children and Adults Tai Chi Study (CF-CATS2): a randomised controlled feasibility study comparing internet-delivered with face-to-face Tai Chi lessons in cystic fibrosis

Abstract: Virtual healthcare is fast entering medical practice. Research into the feasibility of using it to teach treatment regimens such as exercise has not been explored. Maintaining an exercise regime can be difficult in cystic fibrosis: group classes risk potential infection, yet motivation is hard to maintain when alone. Tai Chi is a low-impact exercise and involves gentle, demanding movements. This study aimed to assess the feasibility, safety and acceptability of learning Tai Chi via an internet-based approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…Objective quantitative data on changes in physical health as measured by the CFQ-R, PSQI, FFQM, CAMM and clinical data was comparable for both groups [13] . The focus groups and interviews (qualitative data) suggested that the internet group reported better outcomes for breathing, although the quantitative data (CFQ-R) did not bear this out.…”
Section: Data Collectionmentioning
confidence: 85%
See 4 more Smart Citations
“…Objective quantitative data on changes in physical health as measured by the CFQ-R, PSQI, FFQM, CAMM and clinical data was comparable for both groups [13] . The focus groups and interviews (qualitative data) suggested that the internet group reported better outcomes for breathing, although the quantitative data (CFQ-R) did not bear this out.…”
Section: Data Collectionmentioning
confidence: 85%
“…Although full details on inclusion and exclusion criteria, recruitment and participants included in this study have previously been published [ 13 , 14 ]. The study flow chart is provided in Figure 2 .…”
Section: The Studymentioning
confidence: 99%
See 3 more Smart Citations